2002
DOI: 10.1007/s00299-002-0459-7
|View full text |Cite
|
Sign up to set email alerts
|

Efficient recovery of transgenic plants through organogenesis and embryogenesis using a cryptic promoter to drive marker gene expression

Abstract: Our previous studies have shown that tCUP, a cryptic promoter from tobacco, functions in all living plant cell types in a wide range of plant species. This led us to investigate if an enhanced derivative, EntCUP∆, could be used to drive the neomycin phosphotransferase II (nptII) gene and select for kanamycin resistance in crop species that regenerate by organogenesis or embryogenesis. Tobacco (leaves), cauliflower (hypocotyls) and alfalfa (leaves, petioles, stems) explants were co-cultivated with Agrobacterium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 16 publications
0
15
0
Order By: Relevance
“…It was reported that the tCUP sequence could direct transgene expression in both dicots and monocots, but the expression level of the reporter gene seemed lower in monocot cell suspensions than in dicot leaf tissue as measured by the numbers of GUS-positive spots [22]. Although enhanced tCUP derivatives had been used to drive the neomycin phosphotransferase II ( NPTII ) gene and selection for kanamycin resistant transformants in tobacco, cauliflower, alfalfa and Arabidopsis [26,27], the performance of these elements in rice was not known. We therefore examined its expression style and strength in rice and using it for selection of transformants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was reported that the tCUP sequence could direct transgene expression in both dicots and monocots, but the expression level of the reporter gene seemed lower in monocot cell suspensions than in dicot leaf tissue as measured by the numbers of GUS-positive spots [22]. Although enhanced tCUP derivatives had been used to drive the neomycin phosphotransferase II ( NPTII ) gene and selection for kanamycin resistant transformants in tobacco, cauliflower, alfalfa and Arabidopsis [26,27], the performance of these elements in rice was not known. We therefore examined its expression style and strength in rice and using it for selection of transformants.…”
Section: Discussionmentioning
confidence: 99%
“…The plant cryptic promoter tCUP conferred strong constitutive expression when fused to a reporter gene in both tobacco and Arabidopsis [22], and was also highly active in a wide range of dicot plants including alfalfa, canola, cauliflower, tomato and pea as well as in conifers [23-25]. The strong constitutive feasibilities of the tCUP promoter made it possible to drive the expression of a selectable marker gene for recovery of transformed plants through both organogenesis and embryogenesis [26], and proved to be a useful alternative to CaMV 35S as it does not interact with tested promoters [27]. Although the expression of tCUP is reported to be minimal in monocot plants such as wheat, barley, maize and oat [22,23,28], we considered that it would be interesting to study the possible expression and application of tCUP in rice.…”
Section: Introductionmentioning
confidence: 99%
“…The tobacco cryptic promoter (tCUP) (Foster et al ., 1999) contains cryptic regulatory elements equivalent to those responsible for the expression of plant genes (Wu et al ., 2003a). Subsequent research has shown that the enhanced tCUP gene expression system generates levels of β‐glucuronidase (GUS) activity exceeding that of the CaMV 35S promoter (Malik et al ., 2002), and provides equivalent levels of selection in kanamycin (Tian et al ., 2002). Replacement of CaMV 35S promoter by either nos or mas promoters can, in some cases, reduce the misexpression of the transgene (Jagannath et al ., 2001; Yoo et al ., 2005); however, the influence of chimeric and plant‐derived promoters on the tissue specificity of transgene expression has not been investigated rigorously.…”
Section: Introductionmentioning
confidence: 99%
“…Transgenic alfalfa plants were obtained via Agrobacterium -mediated transformation using the method well established in our laboratory [37]. Plant transformation was confirmed by PCR using uid gene primers, histochemical analysis and Southern blot analysis (described above).…”
Section: Resultsmentioning
confidence: 99%
“…The tCUP is plant derived promoter which was identified by promoter-trapping technology [29]. This promoter can drive high levels of gene expression in different plant species and in different organs [37], [41]. Regardless of the promoters used, all of the plants developed from desiccated somatic embryos showed GUS expression and the expression levels were comparable to that developed from embryos without desiccation (Figure 3A, B).…”
Section: Resultsmentioning
confidence: 99%